Mathematical Literacy Abilities of Fifth-Grade Students in View of Adversity Quotient in Hands on Activity-Based RME Learning (Unnes Journal of Mathematics Education Research, 2022)
The purpose of this study was to identify patterns of fifth-grade students' mathematics literacy abilities in relation to adversity quotient. This study is a combination form of sequential explanatory study, where quantitative data is the primary data. In this study, the population was class V of the Padarek region, and the sample consisted of SDN Padarek I and SDN Padarek III. The sample was selected by random sampling. The results of the study on hands-on activity-assisted RME learning revealed a correlation between the achievement of each indicator and mathematical literacy. Quitter students may complete one pattern of literacy accomplishment indicators, namely formulating, whereas camper and climber students can fulfill all three patterns, namely formulating, employing, and interpreting. The quitter, camper, and climber process capability patterns meet all achievement indicators, namely communication, mathematizing, representation, devising strategies, using symbols, and using mathematics tools, but the indicators for using mathematics tools and devising strategies have not been optimally achieved. On the basis of the pattern uncovered regarding each student's mathematical literacy ability, it is recommended to maximize learning in order to get better mathematical literacy abilities.